Morphology and time evolution of thermal jets associated with low-mass young stars - Ainsworth, Rachael Evelyn (Trinity College (Dublin, Ireland). School of Physics, 2016)
Jets are one of the most ubiquitous processes in the Universe, observed from astrophysical objects spanning an extreme range of masses. Despite the difference in scale, the similar morphologies and other characteristics between astrophysical jets suggest that the launching mechanism may be universal, although this suggestion is still controversial. It is widely accepted that many astrophysical jets, including those from young stars, are driven by accretion and launched through magnetohydrodynamic (MHD) processes, in particular, the centrifugal acceleration of material along magnetic field lines anchored to a rotating disk. However, many open questions remain: Where is the precise origin of jet launch? What is the role of the magnetic field? How does the jet evolve with time? These questions are best answered within the domain of low-mass star formation, as the large numbers of (relatively) nearby young stellar objects (YSOs) uniquely allows the region of jet launch to be studied. The latest generation of radio interferometers are the prime instruments to examine this region as they possess high angular resolution, improved sensitivity and can penetrate the encompassing circumstellar material. The aim of this thesis is to investigate the jets driven by young stars over a wide range of radio frequencies and angular resolutions to study the role of their outflows on all scales and how they evolve with time. Data at well-sampled frequencies are crucial to precisely model and differentiate between competing emission mechanisms. Firstly, I investigate a sample of Class 0–I YSOs at 16GHz with low spatial resolution with the Arcminute Microkelvin Imager (AMI) to explore these protostellar systems on large scales where the outflow has interacted with the surrounding envelope and/or molecular cloud. I subtract the contribution of the circumstellar material from the radio luminosity through modelling of the spectral energy distributions and show that free–free emission produced by the jet is the dominant mechanism responsible for the radio emission in this sample. I next extend this investigation to sub-arcsecond scales at 5GHz with the highest angular resolution observations to date of the Class II YSO, DG Tau, taken with the expanded Multi-Element Radio Linked Interferometer Network (e–MERLIN). With these data I measure the initial opening angle of the DG Tau jet, a vital constraint for the origin of MHD jet launch, and demonstrate that the jet is initially generated as a poorly collimated wind which then becomes collimated on scales of 50 au. I calculate the mass-loss rate in the ionised component of the DG Tau jet and find it compatible with MHD disk-wind theory. Finally, I explore a spatial scale intermediate to AMI and e–MERLIN with observations of Class I–II YSOs taken with the Giant Metrewave Radio Telescope (GMRT) at 325 and 610 MHz, which are the first investigations of young, low-mass stars at such low frequencies. The most significant result from this investigation is the detection of a prominent bow shock associated with the DG Tau outflow which exhibits a synchrotron spectrum. This result provides tentative evidence for the acceleration of particles to relativistic energies due to the shock impact of this otherwise very low-power jet against the ambient medium which suggests the possibility of low energy cosmic rays being generated by young Sun-like stars.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin